STRUKTUR KOMUNITAS TUMBUHAN AIR DI DANAU REGEI KELURAHAN TUMBANG TAHAI KECAMATAN BUKIT BATU KALIMANTAN TENGAH: The Structure Of The Aquatic Plant Community In Regei Lake Tumbang Tahai Village Bukit Batu District Central Kalimantan - Suraya, Ummi; Elvince, Rosana; Wati Pakpahan, Penny; Wulandari, Linda (Jurusan Perikanan Fakultas Pertanian Universitas Palangka Raya (UPR), 2025)
This study aims to determine the types of aquatic plants, the structure of aquatic plant communities and water quality in Lake Regei. This study was conducted for 1 (one) month, namely in June 2024. in Lake Regei, Tumbang Tahai Village, Bukit Batu District,Central Kalimantan. The sampling method was carried out by purposive sampling, namely sampling was carried out at 3 (three) stations that were considered important and could represent the water conditions in Lake Regei. The results found that there were three types of aquatic plants, namely kiambang (Salvinia molesta), walingi (Cyperus elatus), and rasau (Pandanus helicopus), with a total of 6,699 individuals. The structure of the aquatic plant community in Lake Regei shows that the density of aquatic plants ranges from 450.75–641.50 ind/m2. The diversity index value (H’) ranges from 0.224-0.234 which is classified as a low diversity value. The uniformity index (E) value of aquatic plants in Lake Regei ranges between 0.204-0.246 indicating that the uniformity of the number of individuals in each species is uneven and very different. The dominance index (D) value of aquatic plants in Lake Regei ranges between 0.897-0.904 indicating that the dominance in the waters of Lake Regei is relatively high. The water quality conditions, namely the values ​​of the Physics and Chemistry parameters in Lake Regei show average values, namely, temperature values ​​ranging from 28 -32.85⁰C, brightness ranging from 10.8-12.5 cm, depth ranging from 1.05-3.15 m, turbidity ranging from 24.5-71.0 NTU, acidity (pH) ranging from 5.68-6.2, dissolved oxygen ranging from 6.1-6.8 mg/l, nitrate ranging from 0.005-0.007 mg/l and phosphate ranging from 0.025-0.069 mg/l.